2004
DOI: 10.1111/j.1360-0443.2004.00654.x
|View full text |Cite|
|
Sign up to set email alerts
|

Serious adverse events in the Australian National Evaluation of Pharmacotherapies for Opioid Dependence (NEPOD)

Abstract: Individuals who leave pharmacotherapies for opioid dependence experience higher overdose and death rates compared with those in treatment. This may be due partly to a participant self-selection effect rather than entirely to pharmacotherapy being protective. Clinicians should alert naltrexone treatment patients in particular about heroin overdose risks. Duty of care may extend beyond cessation of dosing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 49 publications
4
79
1
2
Order By: Relevance
“…These withdrawal symptoms may have resulted from voluntary or forced periods of abstinence, including incarceration or drug treatment attempts, although we did not find an independent effect of enrollment in detoxification in the past six months on the risk of recent overdose, as demonstrated in other studies. 23 In this sample, younger heroin injectors were at greatest risk of experiencing a recent overdose. Although this finding has been replicated in at least one other study, 7 most studies have indicated greater risk of overdose among older users.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These withdrawal symptoms may have resulted from voluntary or forced periods of abstinence, including incarceration or drug treatment attempts, although we did not find an independent effect of enrollment in detoxification in the past six months on the risk of recent overdose, as demonstrated in other studies. 23 In this sample, younger heroin injectors were at greatest risk of experiencing a recent overdose. Although this finding has been replicated in at least one other study, 7 most studies have indicated greater risk of overdose among older users.…”
Section: Discussionmentioning
confidence: 99%
“…Length of drug use, 4,15 polydrug use, 4,[16][17][18] risky drug use, 13,15,19 disrupted life circumstances, 20,21 and conflicts within social networks 19 are associated with overdose. Risk of overdose increases with periods of reduced tolerance, including release from prison 22 and naltrexone detoxification, 23 while overdose risk is decreased with agonist maintenance therapy 24 ; opioid metabolites in the hair of overdose decedents are far below the levels of active heroin users, 25,26 suggesting periods of abstinence preceding death. Drug dependence may have a more complicated relationship with overdose, with heroin dependence possibly protecting users through increased tolerance and cocaine dependence resulting in direct toxicity.…”
mentioning
confidence: 99%
“…Although opioid antagonists up‐regulated μ‐receptors and induced supersensitivity to morphine in a mouse model,91 healthy humans show no evidence of μ‐receptor up‐regulation in the respiratory control system, the most likely site of opioid overdose lethality 92. Overall, the risk of overdose is significantly lower in patients who are actively involved in medication‐assisted treatment whether it is with methadone, buprenorphine, or naltrexone 93. Attempts to override the antagonist blockade, however, can result in fatal overdose,11 which should be discussed with patients at each treatment visit.…”
Section: Current Approach To Treatment Of Opioid Use Disorder: Choosimentioning
confidence: 99%
“…Secondly, there are doubts about the safety of oral naltrexone in treating unselected opioid-dependent patients. Its acute toxicity may indeed be low [5], but the risk of fatal opioid overdose is doubled when patients stop taking naltrexone and return to opioid use, as most of them do [11,12]. A drug that is no better than placebo in unselected opioid-dependent patients and that doubles the risk of overdose when these patients stop using it does not have strong claims to being safe and effective.…”
Section: How Safe and Effective Are Naltrexone Implants?mentioning
confidence: 99%